2021
DOI: 10.1016/j.ejmp.2021.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Breast glandularity and mean glandular dose assessment using a deep learning framework: Virtual patients study

Abstract: Breast dosimetry in mammography is an important aspect of radioprotection since women are exposed periodically to ionizing radiation due to breast cancer screening programs. Mean glandular dose (MGD) is the standard quantity employed for the establishment of dose reference levels in retrospective population studies. However, MGD calculations requires breast glandularity estimation. This work proposes a deep learning framework for volume glandular fraction (VGF) estimations based on mammography images, which in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Tables of D g N CT values are usually calculated with the homogeneous tissue approximation (i.e., where the phantom tissue is a homogeneous mixture of adipose and glandular tissues of given glandular fraction by mass), but they have been calculated also for anthropomorphic voxelized breast phantoms, where the voxels are either 100% adipose or 100% glandular, spatially distributed realistically in the breast phantom at a given value of glandular fraction . For DM and DBT dosimetry, the former approach was also adopted in Massera et al (2021aMassera et al ( , 2021b, Sarno et al (2021), Caballo et al (2022). Here, we adopt the latter method (as in Sarno et al 2022 and Mettivier et al 2022), using our set of patient-derived anthropomorphic breast phantoms.…”
Section: Air Kerma and D G N Ct Evaluationmentioning
confidence: 99%
“…Tables of D g N CT values are usually calculated with the homogeneous tissue approximation (i.e., where the phantom tissue is a homogeneous mixture of adipose and glandular tissues of given glandular fraction by mass), but they have been calculated also for anthropomorphic voxelized breast phantoms, where the voxels are either 100% adipose or 100% glandular, spatially distributed realistically in the breast phantom at a given value of glandular fraction . For DM and DBT dosimetry, the former approach was also adopted in Massera et al (2021aMassera et al ( , 2021b, Sarno et al (2021), Caballo et al (2022). Here, we adopt the latter method (as in Sarno et al 2022 and Mettivier et al 2022), using our set of patient-derived anthropomorphic breast phantoms.…”
Section: Air Kerma and D G N Ct Evaluationmentioning
confidence: 99%
“…Its estimation requires measurements of breast density, air kerma and Monte Carlo-based conversion coefficients. By use of deep neural networks Tomal et al [19] showed that both volumetric breast glandularity and mean glandular dose could be automatically assessed. The system was thoroughly validated by virtual anthropomorphic breast phantoms and other tools available in the literature.…”
Section: Ai Applications In Rx Mammographymentioning
confidence: 99%
“…Such a homogeneous breast model is a simplification of the real condition of a 3D heterogeneous distribution of the glandular mass in the patient breast. MGD is adopted in worldwide quality assurance protocols both in DM and in DBT for assuring the accomplishment of regulatory dose limits and for imaging unit performance assessment [12][13][14][15][16] as well as for comparison of different solutions (DM vs DBT vs BCT) [17][18][19][20]. However, the adoption of MGD as a unique metric for dose assessment has critical aspects, both for its use in patient dose estimates and for the comparison of dose level of different imaging modalities.…”
Section: Introductionmentioning
confidence: 99%